Penerapan Metode SAW (Simple Additive Weighting) Dalam Pemilihan Siswa-Siswi Berprestasi Pada Sekolah SMK Swasta Mustafa - Ramadhan, Muhammad Rizky; Nizam, Muhammad Khairul; Mesran, Mesran (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
In the face of the times and the era of technology that is rapidly developing at any time, the development of human resources is a top priority in the national development of the state, the position and position of students, has a very important role in teaching and learning activities for students to improve. Student achievement in academics and non-academic fields, one of the things that motivates students to always develop themselves is to give an award as an outstanding student with the criteria determined by the school. Temporary observations at Mustafa Private Vocational High School in determining outstanding students were done manually. This method is still considered ineffective and inefficient. Based on this, a model for determining outstanding students at Mustafa Private Vocational School is needed with a more efficient and effective system. This system is designed using a decision support system through the Simple Additive Weighting (SAW) method. This system can display the results of the ranking of outstanding students based on the calculation results of the SAW method